2016
DOI: 10.2147/ndt.s118614
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dopamine D2 receptor gene polymorphisms and schizophrenia risk: a PRISMA compliant meta-analysis

Abstract: ObjectiveTo determine the relationships between dopamine D2 receptor gene polymorphisms and the risk of schizophrenia using meta-analysis.MethodThe PubMed, Embase, and China National Knowledge Infrastructure databases were searched to identify relevant literature published up to February 2016. The allele contrast model was used. Stata software was used for statistical analysis, with odds ratios (ORs) and 95% confidence intervals (CIs) calculated to evaluate the associations between dopamine D2 receptor gene po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 74 publications
0
23
1
Order By: Relevance
“…However, the approach is vulnerable to the effect of racial stratification, sample population, and sample content. Sample population issues may also explain the inconsistencies between our results and some meta‐analyses conducted in Asia (He et al, ; Wang et al, ) and even in China (Zhao et al, ). China is a vast country with a great geographical distance between north and south.…”
Section: Discussioncontrasting
confidence: 58%
“…However, the approach is vulnerable to the effect of racial stratification, sample population, and sample content. Sample population issues may also explain the inconsistencies between our results and some meta‐analyses conducted in Asia (He et al, ; Wang et al, ) and even in China (Zhao et al, ). China is a vast country with a great geographical distance between north and south.…”
Section: Discussioncontrasting
confidence: 58%
“…On the contrary, Vijayan et al reported higher frequency of Cys311 in South Indian schizophrenia patients 26 . A recent meta‐analysis of 42 case‐control studies revealed positive association of DRD2 SNP (rs1801028, C/G) with schizophrenia and sub‐group analysis showed that G‐allele was associated with increased susceptibility to schizophrenia in Asians 15 . On the contrary, there are also meta‐analysis that have reported no association of rs1801028 with schizophrenia 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients carrying Cys311 variant are less likely to be hospitalised, have lesser negative symptoms, shorter duration of hospitalisation and also respond better to antipsychotics 14 . However, some of the studies have reported positive association of this polymorphism with schizophrenia in various populations, 15,16 Further, few studies have also reported no association of this polymorphism with schizophrenia 4,11 …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated significant neurobiological effects of the C957T variants on executive function, memory, perception, and processing of cognitive stimuli in clinical and non-clinical populations [12][13][14][15]. The association of C957T with schizophrenia, with the C allele being a risk factor, was confirmed in 2 recent meta-analyses [16,17].…”
Section: Introductionmentioning
confidence: 87%